PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN BAGIAN GUDANG PADA PT PULAU BARU JAYA - Sri Mulyani; Ni Nyoman Suarniki; Muhammad Yusuf Ilmi (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2021)
This study aims to determine the effect of occupational safety and health programs on the work productivity of PT Pulau Baru Jaya employees. The population in this study is the total number of employees in the Warehouse section at PT Pulau Baru Jaya, which totals 68 employees. According to Arikunto (2006: 120) "If the total population is less than 100 then the sample taken is the entire population". In this study, the samples taken were all warehouse employees, totaling 68 people. The results of the research conducted with partial regression analysis using SPSS for Windows version 22.0. Work safety (X1) and occupational health (X2) variables have an influence on employee productivity (Y). In the occupational safety (X1) and occupational health (X2) variables, the occupational health variable (X2) has the most dominant influence on work productivity (Y). The Adjusted R Square value is 0.204 or 20.4% which means that the employee productivity variable (Y) is influenced by the occupational safety (X1) and occupational health (X2) variables of 20.4% where the independent variables in explaining the variation of the dependent variable are very limited and the remaining 79.6% was influenced by other factors not studied.